2013
DOI: 10.1016/j.ejor.2012.08.015
|View full text |Cite
|
Sign up to set email alerts
|

A review of dynamic vehicle routing problems

Abstract: A number of technological advances have led to a renewed interest on dynamic vehicle routing problems. This survey classifies routing problems from the perspective of information quality and evolution. After presenting a general description of dynamic routing, we introduce the notion of degree of dynamism, and present a comprehensive review of applications and solution methods for dynamic vehicle routing problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
542
0
9

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 984 publications
(553 citation statements)
references
References 137 publications
(211 reference statements)
2
542
0
9
Order By: Relevance
“…A report summarizes the results of a literature review on dynamic vehicle routing problems, supported by example of real-world applications of such problems, draws a detailed study of the current state of the art in dynamic vehicle routing optimization (Pillac, Guéret & Medaglia, 2010). A newly survey classifies routing problems from the perspective of information quality and evolution, introduces the notion of degree of dynamism, and presents a comprehensive review of applications and solution methods for dynamic vehicle routing problems (Pillac, Gendreau, Guéret & Medaglia, 2013). Current and more researches on the logistics vehicle routing optimization are considered from the perspective of cost savings, such as Cao, Zheng, Li, Yang and Lian (2008).…”
Section: Introductionmentioning
confidence: 99%
“…A report summarizes the results of a literature review on dynamic vehicle routing problems, supported by example of real-world applications of such problems, draws a detailed study of the current state of the art in dynamic vehicle routing optimization (Pillac, Guéret & Medaglia, 2010). A newly survey classifies routing problems from the perspective of information quality and evolution, introduces the notion of degree of dynamism, and presents a comprehensive review of applications and solution methods for dynamic vehicle routing problems (Pillac, Gendreau, Guéret & Medaglia, 2013). Current and more researches on the logistics vehicle routing optimization are considered from the perspective of cost savings, such as Cao, Zheng, Li, Yang and Lian (2008).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in the recent literature have shown that waiting can be a useful strategy in handling dynamic customer arrivals, especially those with time windows [21]. In this section, we first review two common waiting time adjustment strategies for the vehicle routing problem with time windows, namely the Push Backward and Push Forward heuristics.…”
Section: Waiting Time Adjustmentmentioning
confidence: 99%
“…This cannot be done without the help of real-time vehicle positioning and communication technologies. Due to recent advances in these technologies, they can now be implemented at lower costs and at a larger scale [21]. One can refer to [6,14,21] for complete reviews on the recent literature on the vehicle routing problems, and [23,24] for stochastic and dynamic vehicle routing problems.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the modelling and algorithmic approaches used to address a dynamic vehicle routing problem may provide useful insights for disruption management in vehicle routing and scheduling. Pillac et al (2013) present a review of the Dynamic Vehicle Routing Problems (DVRPs) with more than 150 references. That study classifies routing problems from the perspective of information quality (deterministic versus stochastic input) and evolution of information (whether or not the information available to the planner may change during the execution of the routes).…”
Section: : "At the Beginning Of A Business Cycle An Optimal Or Near-mentioning
confidence: 99%